Implementasi Nilai Pendidikan dan Ilmu Pengetahuan yang Terkandung dalam Al-Qur’an - Fitriana Yasintha; Muhammad Ari Khairan; Muhammad Taura Zilhazem; Muhammad Iqbal Ramadhan; Muthia Azzahra; Fathur Rahman; Almer Ragil Amri (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This study aims to examine and understand the verses of the Koran related to technology and innovation and to analyze the implications of these interpretations for the development of science in the modern era. Al-Qur'an as a holy book for Muslims is considered as a source of law and a way of life that covers various aspects of life, including the development of science and technology. The research method used is analysis of the contents of the newspaper, namely by identifying and studying verses that talk about technological developments and innovations. Interpretation of these verses will be carried out through contextual and historical interpretation approaches, and taking into account the views of religious scholars and experts. The results of this research are expected to provide a deeper understanding of the Qur'an's views on technology and innovation, and how these views can be applied in the context of science in the modern era. The implications of the interpretation of these verses will help direct the development of science and technology in accordance with Islamic values, uphold ethics, provide benefits for humanity as a whole, and invite people to develop their own creative thinking ideas. It is hoped that the results of this research can contribute to strengthening the integration between religion and science, as well as providing guidance for scientists and researchers in developing technology and innovation that are responsible and in accordance with the moral values.